Hyperinsulinaemic hypoglycaemia. Issue 6 (4th February 2009) - Kapoor, R R; Flanagan, S E; James, C; Shield, J; Ellard, S; Hussain, K
Abstract : Hyperinsulinaemic hypoglycaemia (HH) occurs as a consequence of unregulated insulin secretion from pancreatic β cells. In the newborn period it is the most common cause of severe and persistent hypoglycaemia. As HH is a major risk factor for brain injury and subsequent neurodevelopment handicap, the identification, rapid diagnosis and prompt management of patients with HH is essential if brain damage is to be avoided. Advances in molecular genetics, radiological imaging techniques (such as fluorine-18 L-3, 4-dihydroxyphenylalanine positron emission tomography ( 18F DOPA-PET) scanning) and laparoscopic surgery have completely changed the clinical approach to infants with the severe congenital forms of HH. This review gives an outline of the clinical presentation, the diagnostic cascade, the underlying molecular mechanisms and the management of HH with a particular focus on congenital forms of hyperinsulinism.